Human aspects of quality practices and governance on the performance of revenue collection agencies in Malaysia - Mukhtar, Ramlah (2013)
Quality management initiatives are widely implemented as tools for performance improvement in many organizations including service organizations. Yet, failures are associated with their implementations whereby not all quality management initiatives give desired improvement in performance. Current knowledge is also limited in providing insights on the significance of quality governance as a factor for enhancing performance. This study aims to investigate the potential effect of quality governance for successful implementation of quality management initiatives in public service sector, integrated with the impact of HR infrastructure quality practices on organizational performance. A proposed research framework and hypotheses are tested using primary data through crosssectional survey from a sample of 315 managers in the revenue collection agencies in Malaysian public service sector. The results derived from structural equation modelling (SEM) testing evidently indicate the associations of quality governance with HR infrastructure quality practices and organizational performance. The findings of this study also prove that the hypothesized model attested the significance of quality governance as a factor for performance improvement and its significant role as a mediating factor in the relationship between HR infrastructure quality practices and organizational performance. Top management commitment was found to be the key HR infrastructure quality practice to ensure the existence of quality governance for better performance. Employee empowerment,employee training, and customer focus are also significant for enhancing quality governance to improve organizational performance. The findings further suggest that performance improvement is realizable whenever customer focused practices are emphasized. Consequently, the public revenue collection agencies should be aware of the importance of having effective HR infrastructure quality practices, especially the ones which are more customer focused, to promote quality governance in enhancing organizational performance. This study also advances the understanding on the importance of quality governance in relation to human factors in the quality management research. Particularly, this study suggests that future research efforts should be extended in taking up the issues related to quality governance to provide better perspectives in quality management research in different sectors or other contexts.